EDUKASI LAPORAN KEUANGAN DAN PROMOSI DIGITAL PADA USAHA AYAM GEPREK SAMBAL PETIR DI SERANG BARU KABUPATEN BEKASI - Widati, Sindik; Pujia, Dede Puspa; Mahendra, Dheni Muhammad; Windi, Windi; Syalsabilla, Syalsabilla (Universitas katolik Musi Charitas, 2024)
Micro, Small, and Medium Enterprises (MSMEs) have an important role in a country's economy, including in Indonesia. However, MSMEs often face challenges in increasing their competitiveness during increasingly fierce global competition, especially after the Covid-19 pandemic which made people build businesses in the culinary field. Things that can help MSMEs increase their competitiveness are the use of information technology or social media. The community service partner is the Ayam Geprek Sambal Petir business in Bekasi Regency. The obstacles include limited knowledge in calculating and preparing financial reports and not understanding how to promote their business using social media. The solution to these problems is to provide education about financial reports and business promotion using social media. The implementation method is in the form of lectures, discussions, simulations and implementation of financial reports and the use of social media. The activity results show that partners can compile financial reports independently with the help of the Sepran application and can create promotional content using social media.